(untitled) (diségno, 2023)
The Stelvio pass hosts treasures that tell the story of the Great War. Remains hidden for more than a century in the ice of peaks of more than 3.000 meters altitude and revealed today following the gradual increase in temperatures. Complex of small fortifications, trenches, artillery sites and tunnels for the shelter of troops and vehicles. They testify to the violent clashes between the mountain ranges of Ortles-Cevedale, Tonale and Adamello. An integrated system where the military architecture blends with the landscape and camouflages itself with the materials and colors of the high-altitude environment; the rock is transformed into buildings to accommodate the spaces and functions necessary for the survival of men. A story little told but useful to make known another ‘viewpoint’ of the conflict to spread and communicate also with the tools of the Science of Drawing. The surveyor thus has the task of rendering, thanks to the graphic representation, the measurement of the territory and the representation of the landscape. The essay presents the results of a historical-architectural and landscape study that included the virtual reconstruction of the fortification of the pass: from the acquisition carried out with UAV systems to the return through 3D modelling. A particular place that the direct investigation and the electronic eye of the sensors, which from the top of the sky can read the particularity hidden among the high peaks, have allowed to perceive and document to preserve its physical substance and memory.